2017
DOI: 10.1177/2382120517721901
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Revised Curriculum on Academic Motivation, Burnout, and Quality of Life Among Medical Students

Abstract: Objective:The purpose of this study was to determine the impact of a revised curriculum on medical student academic motivation, burnout, and quality of life.Methods:This cross-sectional comparative study involved 2 medical school cohorts of second year and fourth year medical students at The University of Auckland: a cohort under a traditional curriculum (n = 437) and a cohort under a revised curriculum (n = 446). Participants completed self-reported questionnaires measuring academic motivation, burnout, and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…This finding is in line with that of earlier studies which have shown a significantly higher deep learning approach among medical students [9][10][11]. However, changes in curricular delivery may not always result in an apparent change in the student learning approach [12,13]. It is important to determine how the students perceive the changes in the curriculum, and how these changes affect their academic motivation and quality of life [13].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding is in line with that of earlier studies which have shown a significantly higher deep learning approach among medical students [9][10][11]. However, changes in curricular delivery may not always result in an apparent change in the student learning approach [12,13]. It is important to determine how the students perceive the changes in the curriculum, and how these changes affect their academic motivation and quality of life [13].…”
Section: Discussionsupporting
confidence: 86%
“…However, changes in curricular delivery may not always result in an apparent change in the student learning approach [12,13]. It is important to determine how the students perceive the changes in the curriculum, and how these changes affect their academic motivation and quality of life [13]. Moreover, the learning approach may change over time.…”
Section: Discussionmentioning
confidence: 99%
“…Student feedback in course evaluations regularly cited these approaches as making subjects “easier to understand.” In contrast, use of single pedagogies such as problem‐solving or team based learning approaches have potential benefits in developing student cognition but at the expense of increasing stress (White et al, 2014). While changes in methods of assessment have been indicated to improve student well‐being (Bloodgood, Short, Jackson, & Martindale, 2009; Wilkinson, 2011) there have been few proposals for changes in pedagogy to reduce stress (D'Eon, 2014; Lyndon et al, 2017). The present study suggests that establishing and directly assessing a vocabulary and base of anatomical knowledge can facilitate learning that can be applied to more complex clinical problems, with a concomitant and overall decrease in stress.…”
Section: Discussionmentioning
confidence: 99%
“…Undergraduate medical training and residency training are high-risk periods for burnout worldwide. 4,5 A study of burnout in pediatrics residency training in England found that trainees with burnout condition had suboptimal patient care attitudes and behaviors which were discharging patients to make the service more manageable, not thoroughly discussing treatment options or answering questions, making treatment or medication errors, ignoring the social or personal impact of an illness and feeling guilty about how a patient was treated. 6 In Thailand, the research of Srikam et al 7 found that 5.63% of residents had burnout condition.…”
Section: Introductionmentioning
confidence: 99%